Do silêncio emerge um grito: O governo Revolucionário cubano e as memórias da repressão sexual nas Umaps (2007-2020) - Rodrigues, Amanda Aparecida Gomes (2024)
In the 1960s, the Military Units for Production Aid (Umaps) emerged in Cuba. Officially, they were agricultural labor centers whose purpose was to recruit young people considered unfit for military service. However, during their period of existence there were accusations that they were functioning as prisons for the sexually "deviant," religious groups, hippies, and political prisoners. Taking this into account, this research seeks to analyze – without losing sight of the necessary critical perspective - testimonies of former Umapsians, between 2007 and 2020, about the experiences of homosexuals and counterrevolutionaries who were confined in the Umaps and suffered with the repression practiced by the Cuban government implanted in 1959. To this end, the blogs Generación Y, by Yoani Sanchez, and UmapCuba1965, by an association of former inmates, with executive direction by Francisco García Martinez, will be examined, as well as the newspapers 14ymedio and Diario de Cuba, which have received contributions from various authors. Another source will be the book Umap: una muerte a plazos, by José Caballero Blanco. Thus, we will seek to emphasize the battles of memories in the midst of political disputes, trying to ascertain simultaneously the interests that drive the action of the former Umapians and their ideology.